Defisiensi Vitamin D sebagai Salah Satu Faktor Risiko Kematian pada Pasien COVID-19: Studi Tinjauan Pustaka - Syafarudin Nur; Mondastri Korib Sudaryo; Nurul Fajri Widyasari (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is a new infectious disease and to date become a global pandemic. COVID-19 has symptoms varies in severity from mild to severe and can be fatal. Vitamin D deficiency could affect individual's immunity and increase the risk of mortality in COVID-19 patients.Methods: We did a literature review study to describe the association between vitamin D deficiency and mortality in COVID-19 patients. Literature search was done using PubMed database with keyword â€œCOVID-19â€ AND â€œVitamin D Deficiencyâ€ AND â€œOutcomeâ€. Articles published before June 30th 2021 and published in English language were included in this study. Inclusion criteria is case control or cohort study which evaluate association between vitamin D deficiency and mortality in COVID-19 patients.Result: 13 eligible articles which met inclusion and exclusion criteria were included in this study. All subjects in included studies were COVID-19 patients confirmed by laboratory RT-PCR. Mean age of the subjects in included studies were range from 55-79 years old, with proportion of male more than female in most of the studies. 25(OH)D level <20 ng/ml was definition of vitamin D deficiency most often used. Vitamin D deficiency were significantly associated with COVID-19 mortality, with OR in 3 studies range from 3,87-6,84 and HR in 3 studies range from 4,15-14,73.Conclusion: This literature review concluded that vitamin D deficiency had the potency to be risk factor for mortality in COVID-19 patients.